Forced Convection through Discrete Heat Sources and Simple Thermal Model – A Numerical Study - Kartikaswami Hasavimath; Kishan Naik; Banjara Kotresha; N. Gnanasekaran (International Journal of Mathematical, Engineering and Management Sciences, 2019)
In this work a forced convection through discrete heat sources and simple thermal model placed inside the vertical channel is analyzed numerically. The problem considered for the investigation comprises of a vertical channel with distinct heat source assembly located at the center of the channel. The novelty of the present work is to replace the discrete heat source assembly by a simple thermal model to obtain uniformly distributed temperature and streamlines. A conjugate heat transfer investigation is carried out because the problem domain consists of aluminum solid strips as well as Bakelite strips in discrete heat source assembly which are replaced by a aluminum solid in case of simple thermal model. The numerically obtained data are initially compared with experimental data for the purpose of validation. The temperature of each discrete sources decrease with increase in inlet velocity of the fluid and bottom heat source is able to take higher heat load. The results in terms excess temperature obtained for both discrete heat source and simple thermal model is presented and discussed.